Research and Technology Management in the Electricity Industry Methods, Tools and Case Studies - Daim, Tugrul; Oliver, Terry; Kim, Jisun; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Technologies such as renewable energy alternatives including wind, solar and biomass, storage technologies and electric engines are creating a different landscape for the  electricity industry. Using sources and ideas from technologies such as renewable energy alternatives, Research and Technology Management in the Electricity Industry explores a different landscape for this industry and applies it to the electric industry supported by real industry cases.   Divided into three sections, Research and Technology Management in the Electricity Industry introduces a range of  methods and tools including technology assessment, forecasting, roadmapping, research and development portfolio management and technology transfer. These tools are the applied to emerging technologies in this industry with case studies including data from various organizations including Bonneville Power Administration and Energy Trust of Oregon, from sectors including lighting and wind energy. The final section considers innovation through these technologies.   A product result of a collaboration between Bonneville Power Administration and Portland State University, Research and Technology Management in the Electricity Industry is a comprehensive collection of methods, tools, examples and pathways for future innovation in the electricity industry.
Introduction -- 1.Methods and Tools Applied in Strategic Technology Planning -- 2.Multi-criteria Applications in Renewable Energy Analysis, a literature Review -- 3.Expert Judgment Quantification -- 4.Technology Forecasting Methods -- 5.Use of Multiple Perspectives and Decision Modeling for PV Technology Assessment -- 6.Application of Fuzzy Cognitive Map (FCM) for the development of Scenarios: A Case Study of Wind Energy Deployment -- 7.Transmission Technology Needs -- 8.Forecasting the Maturity of Alternate Wind Turbine Technologies through Patent Analysis -- 9.Technology Adoption - Building IT -- 10.Adoption of Energy Efficiency Technologies:  A Review of behavioral theories for the case of LED lighting -- 11.Application of a Cross-Disciplinary Taxonomy: Technology Transfer of Energy Innovations from Government Labs -- 12.A Framework for Green/Eco-Innovation through Use of a Novel Measure: E/R -- 13.Analysis of Some of the Demand Side Management Products at Residential Sites -- 14.Solar Lanterns – Technology Adoption Model for Indian Villages -- 15.Adoption of Energy Efficient Technologies from a Demand Side Management Perspective: Taxonomy of Adoption Drivers, Barriers and Policy tools.
Keywords: Energy harvesting; Renewable energy resources; Management; Industrial management; Engineering economics; Engineering economy; Energy policy; Energy and state; Energy Harvesting; Renewable and Green Energy; Innovation/Technology Management; Engineering Economics, Organization, Logistics, Marketing; Energy Policy, Economics and Management